2019
DOI: 10.1093/jas/skz199
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenic potential of tropical feeds rich in hydrolyzable tannins1,2

Abstract: The present study was carried out to determine the effect of Acacia nilotica, a tropical plant rich in hydrolyzable tannins (HT), on rumen fermentation and methane (CH4) production in vitro. We used leaves and pods from A. nilotica alone and combined. The combination of HT from A. nilotica leaves and pods and condensed tannins (CT) from Calliandra calothyrsus and Leucaena leucocephala were also evaluated to assess potential differences in biological activity between HT and CT. Four series of 24-h incubations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Recently an in vitro study of Saminathan et al (205) showed that tropical legumes having CT with different molecular weights can serve as potential feed additives to mitigate CH 4 production with no adverse effects on rumen fungal microflora and fiber digestion. Contrarily, Rira et al (196) reported that in vitro HT (A. nilotica) are more promising for suppressing methanogenesis than CT (from C. calothyrsus and L. leucocephala). Chestnut tannin possesses sufficient potential to reduce methanogenesis, without compromising feed efficiency and animal performance due to its neutral effect on NDF digestibility (177).…”
Section: Effect Of Tannins On Rumen Methanogenesis and Fermentation Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently an in vitro study of Saminathan et al (205) showed that tropical legumes having CT with different molecular weights can serve as potential feed additives to mitigate CH 4 production with no adverse effects on rumen fungal microflora and fiber digestion. Contrarily, Rira et al (196) reported that in vitro HT (A. nilotica) are more promising for suppressing methanogenesis than CT (from C. calothyrsus and L. leucocephala). Chestnut tannin possesses sufficient potential to reduce methanogenesis, without compromising feed efficiency and animal performance due to its neutral effect on NDF digestibility (177).…”
Section: Effect Of Tannins On Rumen Methanogenesis and Fermentation Cmentioning
confidence: 99%
“…It may be attributed to the fact that HT (e.g., gallic acid subunits) directly inhibit methanogens, but the action of CT on rumen CH 4 production is variable ( 172 , 207 ). However, long-term trials are required to assess the possible adaptation of rumen microbes toward the optimal level of HT and its subunit, gallic acid, to avoid their adverse effects on animal performance ( 196 ).…”
Section: Dietary Manipulation Of Rumen Function Using Natural Feed Admentioning
confidence: 99%
“…However, low MW tannins with GA derivatives or galloylated CT, which, upon degradation, produces GA, may have selective antimethnogenic effects. For example, Rira et al [75] reported that a HT-rich forage was 26% more effective in suppressing methanogenesis in vitro than CT-rich sources.…”
Section: Effects Of Tannins In Ruminant Nutritionmentioning
confidence: 99%
“…Linear (L) and quadratic (Q) responses were analyzed to evaluate the dose-dependent trends. The significant level was p < 0.05, and the highly significant level was p < 0.01 [ 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%